2022
DOI: 10.1007/s11356-022-19213-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4,6-Trichlorophenol on Clarias batrachus: a biomarkers approach

Abstract: Abstract2,4,6-Trichlorophenol (2,4,6-TCP) is a common waste among the resulting chlorophenols generated in the production of common products classified as an extremely toxic, mutagenic, carcinogenic and highly persistent xenobiotic in the environment. To evaluate the impact of 2,4,6-TCP in aquatic systems, the catfish species Clarias batrachus has been selected to test its toxicity due to its high market value and consumption in India. Here is presented the impact of this compound on different physiological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…Similarly, an alteration in TLC has been reported in C. carpio after exposure to chlorpyrifos [ 93 ]. In contrast, it was observed that the results of the present study, corroborate the findings of Mukherjee et al [ 94 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, an alteration in TLC has been reported in C. carpio after exposure to chlorpyrifos [ 93 ]. In contrast, it was observed that the results of the present study, corroborate the findings of Mukherjee et al [ 94 ].…”
Section: Discussionsupporting
confidence: 91%
“…Despite its germicidal properties, prochloraz can cause dysplasia due to its disruptive endocrine properties [9]. Furthermore, the toxicity of trichlorophenol, which is one of the metabolites of prochloraz, has significantly increased [10,11]. Therefore, studies on the determination and dissipation of prochloraz and its metabolites are of great significance for protecting consumers' health.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their widespread use of CPs, residues of such compounds are continuously detected in soils, sediments, surface water, ground water and in the trophic levels of a food chain. There has been an increasing concern towards the adverse effects of chlorophenols towards environmental damage and human health (Mukherjee et al 2022). CPs are categorised in the priority toxic pollutants listed by USEPA (ASTDR, 2007), and have the ability to bioaccumulate in organisms (de Souza et al 2021).…”
Section: Introductionmentioning
confidence: 99%